Spatial and temporal epidemiology of FMD in Bhutan (2011–2019) - Sangay Letho; Chris Compton (BMC Veterinary Research)
Abstract Background Foot and Mouth Disease (FMD) is an important disease in livestock in Bhutan due to its significant social and economic impacts to the farmers as well as to the government. FMD outbreaks continue to occur every year with greater frequency in some parts of the country despite the implementation of control measures. It is imperative to understand the current patterns of the disease for planning effective control programs. Therefore, this study aimed to investigate the spatial and temporal patterns of FMD in Bhutan since the most recent national survey. Methodology Nine year’s (2011–2019) of national FMD outbreak data was used for this study. An investigation of global spatial autocorrelation was undertaken using the K difference function statistic and local spatial clusters of FMD outbreaks using Kulldorff’s spatial scan statistic. Retrospective spatio-temporal analysis was conducted using a Bernoulli probability model with monthly aggregation of data. A non-stationary cosinor model was used to examine seasonality and trend of outbreaks. Results The K function statistic detected significant global spatial autocorrelation of FMD outbreaks (p < 0.02) and Kulldorff’s spatial scan statistic identified two outbreak clusters in west Bhutan- the first primary cluster (p < 0.002) with relative risk (RR) of 5.22 and radius of 19.77 km in Paro and Thimphu districts and the second primary cluster (p < 0.006, RR = 8.44 radius: 8.98 km) in Punakha and Wangdue Phodrang districts. The spatio-temporal scan test detected a single significant (P < 0.001) space–time cluster of 22 FMD outbreaks centred in south-west Bhutan with a radius of 60 km over an 8-month period in 2018—2019. The temporal analysis indicated that, on an average there were 0.5 (95% CI: 0.2—0.8) additional outbreaks per month in the seasonal winter peaks at 1.9 months (95% CI: 12.55 -3.64) compared with the overall monthly average. Conclusion The western and southern regions of Bhutan have experienced the greatest overall incidence and significant spatial and spatio-temporal clusters of outbreaks of FMD during the period 2011—2019, These findings in districts in the western medium FMD risk surveillance zone threaten progress to control of FMD in Bhutan.